Calibration of end-debonding strength model for FRP-reinforced masonry. (February 2015) - Carozzi, Francesca Giulia; Colombi, Pierluigi; Poggi, Carlo
Abstract: The adherence between Fiber Reinforced Polymers (FRP) reinforcements and masonry is investigated in this paper. Debonding is, in fact, one of the dominant failure modes in the reinforcement of masonry structures by means of FRP materials. Relationships are proposed in design recommendations in order to evaluate the debonding load on the basis of the fracture energy concept. Corrective coefficients are also suggested in order to take into account the effect of bond length and width on the bond strength. In this work experimental double lap push–pull shear tests results are first presented and combined with experimental outcomes from the literature in order to create an enlarged database. An analytical model for the load transfer mechanism between the reinforcement and the substrate is then proposed. Besides, a refined fracture energy based model for the bond strength is suggested taking into account the effect of bond length and width. The experimental outcomes are first used to validate the analytical model for the load transfer mechanism. The enlarged database is then analyzed to achieve a refined statistical calibration of the experimental coefficients of the bond strength model and to highlight the variation of the maximum transmitted force with respect to mechanical properties of the substrate.